Vitrectomy for macular edema due to retinal vein occlusion - Kumagai K (Dove Medical Press, 2019)
Kazuyuki Kumagai,1 Nobuchika Ogino,2 Marie Fukami,1 Mariko Furukawa11Kami-iida Daiichi General Hospital, Aichi, Japan; 2Shinjo Ophthalmologic Institute, Miyazaki, JapanPurpose: To determine the long-term outcomes of vitrectomy for the macular edema associated with a retinal vein occlusion (RVO).Methods: This was a retrospective, consecutive, interventional case series. The intraoperative procedures included internal limiting membrane peeling, arteriovenous sheathotomy, radial optic neurotomy, and intravitreal triamcinolone acetonide injection at the end of the surgery. The main outcome was the best-corrected visual acuity (BCVA).Results: Eight hundred and fifty-four eyes of 854 patients were studied. The eyes consisted of 602 with branch RVO (BRVO), 74 with hemi-central RVO (hemi-CRVO), 87 with nonischemic central retinal vein occlusion (CRVO), and 91 with ischemic CRVO. The mean follow-up period was 68.6 months with a range of 12 to 262 months. The mean BCVA was significantly improved at the final visit (P<0.0001 to 0.0016). The final BCVA improved in 74.4% of the BRVO eyes, in 58.1% of the hemi-CRVO eyes, in 57.4% of the nonischemic CRVO eyes, and in 51.6% of the ischemic CRVO eyes. Multiple regression analysis showed there was no significant relationship between the intraoperative combined procedures and the final BCVA.Conclusions: The results indicate that the type of RVO is significantly associated with the final BCVA, and vitrectomy is a treatment option to improve and maintain BCVA for a long term.Keywords: retinal vein occlusion, vitrectomy, macular edema, internal limiting membrane